Influence of scaler tip designs on tooth surface roughness, tooth substance loss, and patients’ pain perception / Nur Ayman Abdul Hayei - Nur Ayman, Abdul Hayei (2019)
Background: Ultrasonic scalers have been shown effective in removing subgingival calculus. However, it may cause alteration to the tooth surface as well as discomfort to patients. Advances in scaler tip designs may reduce these effects. Limited studies have investigated the influence of scaler tip designs on tooth surface and patients’ comfort. This study comprised of in vitro and clinical investigations, aimed to evaluate the influence of scaler tip designs on tooth surface roughness, tooth substance loss, and patients’ pain perception. Materials and Methods: The in vitro study involved extracted single-rooted sound teeth that were mounted, sectioned, and scaled using PM200 EMS® Piezon, Switzerland; with either (i) Perio Slim (DS-016A) (test) or (ii) conventional scaler tips (FS-407) (control). Tooth surface roughness (n=20) and tooth substance loss (n=46) were measured using a 3D surface texture analyser (Alicona, InfiniteFocus Real3D, Belgium) and scanning electron microscope (SEM) (Quanta-FEG 50, FEI, Germany) respectively, at baseline and following scaling. The clinical study involved a split-mouth design, with 30 participants diagnosed with gingivitis and/or mild chronic periodontitis. The participants were randomly allocated for scaling on quadrant 1 (teeth #13 to #11) and quadrant 2 (teeth #21 to #23); using Perio Slim and conventional scaler tips. Pain perception was recorded using Visual Analogue Scale. Results: Scaling with both scaler tips demonstrated significant reduction in tooth surface roughness following scaling (p < 0.05); but there was no significant difference between the two scaler tips (p > 0.05). Scaling with Perio Slim scaler tip demonstrated significantly less tooth substance loss (p < 0.05) when the initial thickness of the tooth was <1000µm. In the clinical study, the participants reported significantly less pain when scaling was carried out using the Perio Slim scaler tip (median: 3) compared to the conventional scaler tip (median: 5) (p < 0.05). Conclusion: Slimmer scaler tip design (Perio Slim) caused less tooth substance loss and iv less pain than the wider (conventional) scaler tip when used for ultrasonic scaler at medium power setting. Keywords: tooth roughness, tooth substance loss, pain perception, scaler tips